MEASURES COMMERCIAL BANKS HAVE TAKEN TO ENSURE COMPLIANCE WITH THE CAPITAL ADEQUACY REQUIREMENT IN BASEL III FRAMEWORK - Kombo, Kevin N.; Njuguna, Dr. Amos (American Journal of Finance, 2017)
Purpose: The purpose of the study was to establish measures commercial banks have taken to ensure compliance with the capital adequacy requirement in Basel III framework. Methodology: A descriptive survey design was applied to a population of 43 commercial banks operating in Kenya. The target population composed of the 159 management staff currently employed at the head offices of the various commercial banks in Kenya. The population was composed of Senior, Middle and Junior or Entry level Management staff. A sample of 30% was selected from within each group. Primary data was gathered using questionnaires which were dropped off at the bank's head offices and picked up later when the respondents had filled the questionnaires. Descriptive analysis was used to analyze quantitative data while content analysis was used to analyze qualitative data. Results: Based on the findings the study concluded that the commercial banks in Kenya have taken various measures to ensure compliance with capital adequacy requirement such as cutting back on lending, market rights issue/bonds, increasing revenue growth/cutting costs and withholding dividend payment. In addition, the study concluded that commercial banks, in a bid to reduce the challenges experienced in the implementation of capital adequacy requirement, they opt to purchase high quality liquid assets, increasing their maturity profile and increasing retail deposits. Unique contribution to theory, practice and policy: The study recommends that it is vital to understand the forces behind the increasing sophistication and efficiency of risk management systems, before adopting them more widely for regulatory purposes